Headache types and characteristics in patients with Amyotrophic Lateral Sclerosis - Radwa Soliman; Nagia Fahmy; Mahmoud S. Swelam (The Journal of Headache and Pain)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder associated with progressive loss of motor neurons, this result in muscle denervation, atrophy and consequently death takes place due to respiratory failure within 3–5 years of onset of symptoms. Our aim Was to investigate types and frequency of headache in ALS patients. Methods This is cross sectional hospital based study. Clinically definite 100 ALS Patients (diagnosed according to El Escorial revised criteria) were recruited out of 137 ALS patients presented to the Neuromuscular Clinic in Ain Shams university Hospital from February 2022 to June 2024. Patients were screened for headache types and symptoms diagnosed according to International Headache Society criteria (IHS). Headache severity and impact were assessed using Arabic versions of Headache Impact Test (HIT) and Migraine Disability Assessment (MIDAS). Depression was also assessed via Arabic version of Beck's Depression Inventory (BDI). ALS symptoms severity was assessed via Arabic version of Amyotrophic Lateral Sclerosis Functional Rating Scale Revised (ALSFRS-R). Cognitive functions were assessed via the Egyptian version of the Edinburgh Cognitive and Behavioral Amyotrophic Lateral Sclerosis Screen (ECAS‑EG). Demographic data and ALS related parameters were collected. Results Among 100 patients with clinically definite ALS, 79 patients reported headaches, 62 of them had primary headaches; with tension-type headache being the most commonly reported in 46 patients, Migraine in 16 patients. Fifteen ALS patients had secondary headaches; among them 12 had headache secondary to respiratory insufficiency and 3 patients developed headache after the initiation of Riluzole therapy. Two patients had non specific headache. Mean age for the patients at ALS presentation was 43.9 ± 13.8, Mean ALSFRS-R score 33.3 ± 9.04. The relationships between headache and clinical features of ALS were also investigated. In conclusion ALS patients should be evaluated for Headache; Not only headache secondary to respiratory compromise and hypercapnea, but also primary headaches which can be overlooked in patients with ALS.